2010
DOI: 10.1016/j.ejso.2010.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Volume and outcome in colorectal cancer surgery

Abstract: AimsThere is a growing consensus to concentrate high-risk surgical procedures to highvolume surgeons in high-volume hospitals. However, there is fierce debate about centralizing more common malignancies such as colorectal cancer. The objective of this review is to conduct a meta-analysis using the best evidence available on the volume-outcome relationship for colorectal cancer treatment. MethodsA systematic search was performed to identify all relevant articles studying the relation between hospital and/or sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 29 publications
1
63
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] For vascular procedures, increasing surgeon volume has been associated with improved outcomes for carotid endarterectomy, elective open abdominal aortic aneurysm (AAA) repair, open and endovascular repair of ruptured AAAs, thoracoabdominal aortic aneurysm repair, and lower extremity bypass. 1,2,[9][10][11][12][13][14] Recent articles have reported that clinician volume may also affect the outcomes for carotid artery stenting (CAS).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] For vascular procedures, increasing surgeon volume has been associated with improved outcomes for carotid endarterectomy, elective open abdominal aortic aneurysm (AAA) repair, open and endovascular repair of ruptured AAAs, thoracoabdominal aortic aneurysm repair, and lower extremity bypass. 1,2,[9][10][11][12][13][14] Recent articles have reported that clinician volume may also affect the outcomes for carotid artery stenting (CAS).…”
mentioning
confidence: 99%
“…However, two of these papers also come to the conclusion that the impact of volume on outcome 'may be' positive when correlated to HVH [11,12] (these authors found a positive correlation for HVS). The estimation 'maybe' is made by one group only for the category HVS [13], but not for HVH.…”
Section: Colon Cancermentioning
confidence: 99%
“…In CC, two authors each support a positive correlation between volume and treatment quality in favor ('pro') of either HVH [9,10] or HVS [11,12] with respect to short-term outcome. However, two of these papers also come to the conclusion that the impact of volume on outcome 'may be' positive when correlated to HVH [11,12] (these authors found a positive correlation for HVS).…”
Section: Colon Cancermentioning
confidence: 99%
See 2 more Smart Citations